Blogger and Journalist Speech Culture and Word Art - Abdinazarovich, Bazarov Sherali (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides information on the history of speech culture and the art of oratory with specific examples. The article provides information on the theoretical foundations of the culture of speech in the history of mankind, the theory of speech. Here's a few basic facts about a stomp pad and how it is used.